Respon Pertumbuhan Tanaman Gelombang Cinta Akibat Pemberian Pupuk Daun Petrovita di Pembibitan Lanjutan - Djoko Eko Hadi Susilo; Sri Handayani Wahyuningsih (Anterior Jurnal, 2013)
This study aims to determine the growth response of the love wave plant (Anthurium plowmanii) on Petrovita leaf fertilizer in an advanced nursery conducted in August - October 2011 in Panarung Village, Pahandut District, Palangka Raya City. Single treatment design (one factor) with 10 (ten) repetitions in the form of Petrovita leaf fertilizer (D) consisting of 5 concentration levels, namely: d1 = 0.5 ml l-1 (0.05%); d2 = 1.0 ml l-1 (0.10%); d3 = 1.5 ml l-1 (0.15%); d4 = 2.0 ml l-1 (0.20%); and d5 = 2.5 ml l-1 (0.25%) using a completely randomized design. Observations were made when the plants in the advanced nurseries had received treatment applications 4 times at intervals of 2 weeks. Observations were made on plant height (cm); stem height (cm); number of leaves (leaves); leaf length (cm); leaf width (cm); and leaf area (cm2). The results of this study indicate that Petrovita complete leaf fertilizer has a very significant effect on increasing the growth of love wave plants aged 8 MST in advanced nurseries. Petrovita fertilizer concentration of 0.2% or 2 ml l-1 (d4) is the best and most efficient treatment for love wave plants in advanced nurseries. It is recommended to increase the growth of love wave plants in advanced nurseries using Petrovita 0.2% concentration but tried with an interval of less than 2 weeks (for example once a week).